The functional impact on donor vessel following transcatheter closure of coronary artery fistulas—a retrospective study using QFR analysis - Sang, Zhenchi; Ji, Qingqi; Tong, Huan; Shen, Linghong; Wang, Xiaolong; He, Ben (Frontiers in Cardiovascular Medicine, 2024)
Background The impact of transcatheter closure of coronary artery fistula (CAF) and residual shunt after occlusion on improving blood flow in the donor vessel remains uncertain. Objectives To evaluate the functional impact on the donor vessel following CAFs closure using QFR (Quantitative Flow Ratio) analysis. Methods A total of 46 patients with 48 CAFs who underwent transcatheter closure at Shanghai Chest Hospital and Shuguang Hospital between March 2015 and August 2023 were included in the review. The clinical, angiographic details, and QFR data were subjected to analysis. The size of the fistulae was defined according to the ratio between the diameters of the fistulae and the largest diameter of the coronary vessel not feeding the coronary fistula. Results Among 48 CAFs, the average diameter of the fistulae ostium was 3.19 ± 1.04 mm, while the mean diameter of the donor vessel segment following fistulae was 3.45 ± 1.01 mm. The mean QFR value of the donor vessels with medium CAFs was found to be significantly lower than those with small CAFs (0.93 ± 0.10 vs. 0.98 ± 0.03; p < 0.05). Furthermore, the mean QFR value of donor vessels with medium CAFs was observed to be significantly improved after occlusion (0.99 ± 0.01 vs. 0.93 ± 0.10; p = 0.01). However, there was no statistical difference in the mean QFR value of donor vessels with small CAFs before and after occlusion (0.98 ± 0.03 vs. 0.98 ± 0.02; p > 0.05). Moreover, the changes in QFR were more pronounced in donor vessels with medium CAFs compared to those with small CAFs after occlusion (0.06 ± 0.10 vs. 0.005 ± 0.012; p = 0.01). There is no statistical difference in the mean QFR variation and QFR variation rate between donor vessels with CAFs that occurred residual shunt and those without residual shunt after occlusion (p > 0.05). Conclusions The presence of medium CAFs has a significant impact on the blood flow of the donor vessel, as compared to small CAFs, and may benefit from occlusion. A small residual shunt has no significant impact on the effectiveness of CAFs occlusion in enhancing donor blood flow.